Concepção do professor de matemática sobre o ensino da estocástica - Bigattão Junior, Pedro Alceu (2007)
The propositions for the teaching of probability and statistics to the Junior High School suffered successive transformations without, many times, discussions by the teachers that are going to put them into practice. So, the purpose of this study was to verify how the teachers of Junior High School see the stochastic concepts when confronted to the problem situations that involve variability in the exploratory analysis of the data. The bibliographic research for the presenting of the theoretical foundation of the studies was performed. The research methodology was based on the Mathematics teachers conceptions about scholastic teaching. So, a descriptive research was performed, whose data were given by the collaborating teachers. Thus, an inquiry with 23 questions was applied. The analysis of the answers was made with the support of the Classification. Hierarchical Implicative and Cohesive Software (C.H.I.C) that enabled to evidence the inter-relations found on the answers. The study concluded that the teachers researched although teaching the scholastic contents, in the majority of times, without the didactic book or no pedagogical material do not dominate this concept, since no one teaches what they do not know